Beyond COVID19: a creative approach and the used of visual communication design on Amoris hand wash labeling / Nurdarwisyah Balqis Dzuladin - Dzuladin, Nurdarwisyah Balqis (2022)
COVID19 has spread around the world at the time of writing this editorial, with nearly no region remaining unaffected. Due to the rapid spread of COVID19 and the frightening fatality rates, numerous countries and jurisdictions have implemented prevention measures, with hand washing featuring prominently in all of them. During the COVID19 pandemic, hand washing has garnered a lot of attention. Other than that, the attractive visual element on the labeling of hand wash bottle will decide on consumer buying behaviour. As can be seen, the visual is very important because it describes a product soul and understands the information of the product. This research aims is to study the problem of current Amoris labeling design and to propose a new effective visual element and supporting graphic for Amoris hand wash labeling design. Labeling, according to ( Parmar 2006 ), draws the consumer's attention to the product's features and entices them to buy it. It specifically studies for family , a working person and student. 97 of respondent were taken as a sample to gathering all the data about perception towards labeling design. In order to reach a deeper level of comprehension and to ensure that useful information is collected, the researcher used two methods of data collecting as the researcher instrument. Quantitative method ( collecting online data ) and Interview ( exploratory design session ) were used as approaches. The results shows that, a creative approach and used of visual communication design on Amoris labeling hand wash is very successful and make consumer buying behaviour.